SALAFÎ WOMEN AND ISLAMIC MOVEMENTS: The Case of Salafism in Jama‘ah al-Khidhir - Nurani, Shinta (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
One of the ideology and Islamic movement in Indonesia in 1980s was Salafî. This article focuses on a group called Majlis al-Khidhir led by a young Salafist named Abu Ahmad Muhammad al-Khidhir. This article is talking about Salafî women starting to search for and converse of identity as well as their patterns of interest to be Salafî women in carrying out Islamic sharia and the role of al-Khidhir in their lives into Salafîs in accordance with the Quran, hadith, and the attitude of the al-salaf al-ṣâliḥ. The result reveals that the identity and politics of al-Khidhir Salafî women movement has four dimensions. First, Salafî is not a revolutionary movement that opposes Pancasila and especially for Salafî women to obey their husband as ulil amri gives a great responsibility to educate his wife and children. Second, Salafî has different symbols cloths (dress or gamis which covers her body, shows no body shape, not transparent that are plain black from top to bottom, wearing veils or niqâb and socks). Third, Jama‘ah al-Khidhir identified his followers using a familiar greeting, including 'akhi' for men and 'ukhti' for women refer to the symbol of piety and value standards for mutual respect among members of the Salafî community. Fourth, al-Khidhir empowers Salafî women are active in da'wah by using writings and images which are distributed through various media, especially social media WhatsApp, Facebook and Telegram in order to attract the interest of womens to follow the path of al-salaf al-ṣâliḥ.